Efektivitas Kombinasi Pupuk NPK Mutiara dan Pupuk Kandang Ayam terhadap Pertumbuhan dan Hasil Bawang Merah di Lahan Aluvial - Sherly Oktarianti; Setiawan; Ismail Astar; Rini Suryani; Rosalina Yuliana Ayen (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2025)
Shallot (Allium ascalonicum L.) is an important horticultural crop in Indonesia, yet its productivity remains relatively low, especially in suboptimal lands such as alluvial soils. This study aimed to evaluate the effects of combining chicken manure and NPK Mutiara fertilizer on the growth and yield of shallots in alluvial soils of West Kalimantan. The research was conducted from January to March 2025 at the Experimental Garden of the Faculty of Agriculture, Panca Bhakti University, Pontianak, using a factorial Completely Randomized Design (CRD) with two factors: chicken manure (40, 80, and 120 g/polybag) and NPK Mutiara fertilizer (6.22, 7.95, and 9.26 g/polybag). Observed parameters included plant height, number of leaves, number of bulbs, and fresh bulb weight. The results showed that the combination of treatments had no significant effect on all growth and yield parameters. However, the combination of a3n3 (120 g chicken manure and 9.26 g NPK Mutiara) produced the highest average plant height (33.11 cm), while the a2n3 combination resulted in the highest fresh bulb weight (116.67 g). The absence of significant effects is presumed to be due to insufficient nutrient supply under acidic and organic-poor alluvial soil conditions. Further research is needed to determine the optimal dosage and fertilization combination to improve shallot yields on suboptimal land. Recommended to adjust the dosage of chicken manure and NPK Mutiara fertilizer for optimal results, use high-quality seeds with a greater number of active buds, and improve the organic matter content of alluvial soil prior to planting.